A Conceptual and Applied Analysis of the Level 5 Leadership - Karadaş, Halil; Ocak, Mehtap (Fırat University, 2025)
The aim of this research is to examine the conceptual perspective of Fifth Level Leadership and to investigate the leadership behaviors of principals in public schools in terms of Fifth Level Leadership. The phenomenological design, one of the qualitative research methods, was used in the research. The study group consisted of 26 teachers working in various branches in Mardin province in 2022-2023. The data of the research was collected through a semi-structured interview form with six questions. It was revealed that modesty and empathy, which are the characteristic features of Fifth Level Leadership, contributed to teachers' willingness to go to school. In the research, it was determined that teachers who worked with Level Five Leaders went to work happily and peacefully, and their professional self-efficacy was contributed to. According to other results reached in the research, school principals generally exhibit a profile far from Fifth Level Leadership behaviors. The principal profile that teachers want to see is a modest, knowledgeable, postgraduate educated manager who tries to understand teachers, constantly improves himself, is open to communication and cares about appearance.

Bu araştırmanın amacı Beşinci Düzey Liderliğin kavramsal açıdan incelemek ve devlet okullarındaki müdürlerin liderlik davranışlarını Beşinci Düzey Liderlik açısından araştırmaktır. Araştırmada nitel araştırma yöntemlerinden olgubilim deseni kullanılmıştır. Araştırmanın çalışma grubu, 2022-2023 yılında Mardin ilinde, çeşitli branşlarda çalışan 26 öğretmenden oluşmaktadır. Araştırmanın verileri altı soruluk yarı yapılandırılmış görüşme formu aracılığıyla toplanmıştır. Beşinci Düzey Liderliğin karakteristik özelliklerinden alçak gönüllülük ve empati kurmanın, öğretmenlerin istekli bir şekilde okula gitmelerine katkı sunduğu ortaya çıkmıştır. Araştırmada Beşinci Düzey Liderler ile çalışan öğretmenlerin mutlu ve huzurlu bir şekilde işe gittikleri, mesleki öz yeterliklerine katkı sunulduğu tespit edilmiştir. Araştırmada ulaşılan diğer sonuçlara göre okul müdürleri genel anlamda Beşinci Düzey Liderlik davranışlarından uzak bir profil sergilemektedirler. Öğretmenlerin görmek istedikleri müdür profili alçakgönüllü, bilgili, lisansüstü eğitim düzeyi olan, öğretmenleri anlamaya çalışan, kendini sürekli geliştiren, iletişime açık ve dış görünüşe önem veren bir yönetici olması yönündedir.
Beşinci Düzey Liderliğin Kavramsal ve Uygulamalı İncelenmesi
Keywords: Education Policy; Eğitim Politikası